2020
DOI: 10.3390/ijerph17114106
|View full text |Cite
|
Sign up to set email alerts
|

Intensification of Ex Situ Bioremediation of Soils Polluted with Used Lubricant Oils: A Comparison of Biostimulation and Bioaugmentation with a Special Focus on the Type and Size of the Inoculum

Abstract: Used lubricant oils (ULOs) strongly bind to soil particles and cause persistent pollution. In this study, soil microcosm experiments were conducted to model the ex situ bioremediation of a long term ULO-polluted area. Biostimulation and various inoculation levels of bioaugmentation were applied to determine the efficacy of total petrol hydrocarbon (TPH) removal. ULO-contaminated soil microcosms were monitored for microbial respiration, colony-forming units (CFUs) and TPH bioconversion. Biostimulation with inor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 73 publications
(129 reference statements)
0
4
0
Order By: Relevance
“…Biostimulation alone is mostly practiced in soil remediation [ 108 , 109 , 110 , 111 ]. Indigenous micro-organisms remain deprived of nutrients in this natural environment.…”
Section: Bioremediation Methodsmentioning
confidence: 99%
“…Biostimulation alone is mostly practiced in soil remediation [ 108 , 109 , 110 , 111 ]. Indigenous micro-organisms remain deprived of nutrients in this natural environment.…”
Section: Bioremediation Methodsmentioning
confidence: 99%
“…When LNAPL levels drop somewhat as a result of pumping action, the slurp tube removes vapors (vapor extraction) (Speight, 2018). All the liquids (solution of product and groundwater) extracted from a slurp tube are routed to the oil/water separator, while the vapors are routed to the liquid/vapor separator (Bodor et al, 2020).…”
Section: Bio-slurpingmentioning
confidence: 99%
“…The involvement of well-adaptive autochthonous microorganisms is the major advantage of using this approach. Recently, it has been suggested that both these techniques can be also applied ex situ though classified into in situ bioremediation approach [137].…”
Section: Bioaugmentation and Biostimulationmentioning
confidence: 99%